Country-level heterogeneity in MDR-TB drug susceptibility supports country-specific policy development - Fuller, Naomi M.; Davies, Nicholas G.; McHugh, Timothy D.; Knight, Gwenan M. (Frontiers in Tuberculosis, 2025)
ObjectivesThe global challenge of tuberculosis (TB) is exacerbated by multidrug-resistant TB (MDR/RR-TB), confounded by country-level differences in TB prevention and care. The impact of local differences in drug-resistance selection pressure and transmission may be observed by analyzing distributions of minimum inhibitory concentrations (MICs). Using the Bedaquiline Drug-Resistance Emergence Assessment in MDR-TB (DREAM) dataset, we analyzed MIC distributions derived from a standard protocol across 11 countries and 12 antibiotics to explore country-level variation in drug susceptibility.MethodsWe analyzed 71,135 MICs from 5,928 MDR/RR-TB isolates sampled from bedaquiline-naive patients. We compared MIC distributions across countries and WHO resistance classes, then used Spearman rank correlations to compare the drug-susceptibility within individual isolates by country. To explore the effect of bedaquiline use on resistance, we used linear regression to compare bedaquiline MICs with WHO data on bedaquiline usage.ResultsMIC distributions between countries were heterogeneous, especially for fluoroquinolones and isoniazid. The correlation analysis revealed a relationship between bedaquiline and clofazimine MICs in six countries. Analysis of isolates by resistance class demonstrated that XDR-TB isolates had higher MICs than MDR-TB isolates for antibiotics not part of the XDR definition. We found limited evidence to suggest that past bedaquiline usage at the national level led to raised bedaquiline MICs in patients not exposed to the drug.ConclusionsOur research shows clear variations in drug susceptibility within M. tuberculosis across different countries and resistance classes, providing evidence of distinct drug-susceptibility dynamics per country. This expands the evidence for MDR-TB country differences and supports further country-specific policy development.